Pelatihan dan Pendampingan Teknik Pengelasan sebagai Upaya Peningkatan Kemampuan Praktik Siswa SMK Samudera Indonesia Medan - Jandri Fan HT Saragi; Eka Putra Dairi Boangmanalu; Angga Bahri Pratama; Al Qadry Al Qadry; Franklin Taruyun Hudeardo Sinaga (CERED Indonesia Publishing, 2023)
The purpose of this PkM is to provide training and assistance regarding basic welding techniques that are useful for increasing student competence in welding. This training and mentoring in welding techniques serves as a provision for students to enter the world of work and entrepreneurship for SMK graduates as well as assisting the productive process of SMK students who lack funds and practicum facilities to improve their competence in the field of welding. The method used to solve the problems that occur is to use the survey method at SMK to obtain PkM data as needed, formulate training materials, schedule time-related training implementations, arrange instructors who will provide training, make activity evaluation designs, carry out training and mentoring activities Welding techniques were attended by students of SMK Samudra Indonesia, welding teachers, students and lecturers of Mechanical Engineering at the Medan State Polytechnic. The results of the PkM implementation are as follows: Welding skills that can equip SMK students to enter the world of work are being able to operate a welding machine properly and being able to connect plates using welding. The responses from SMK students who took part in the training and assistance from the Medan State Polytechnic Mechanical Engineering Study Program were as follows: they were happy because they had acquired welding skills that they had not mastered to their full potential and the teachers hoped that next year they could continue with other programs.